Flexural Responses of Prestressed Hybrid Wide Flange Composite Girders - Han, Sun-Jin; Lee, Deuck Hang; Oh, Jae‑Yuel; Choi, Seung‑Ho; Kim, Kang Su (SpringerOpen, 2018)
In this study, prestressed hybrid wide flange (PHWF) composite girders were proposed, and full-scale flexural tests were conducted to evaluate their structural performances. This new proposed girder system was developed and designed to effectively resist external loads considering the actual construction sequences. Two specimens with and without shear connectors were fabricated and tested to examine the effect of the shear connectors for achieving the fully-composite behaviors between a cast-in-place (CIP) concrete and the prefabricated prestressed steel–concrete composite girder. The test results showed that sufficient flexural strengths and deformation capacities can be obtained in both types of PHWF composite girders with and without shear connectors. To reflect the actual construction stages of the proposed PHWF composite girder, nonlinear flexural analyses were proposed considering the prestress effect and segmental effect before and after composite with the CIP concrete, respectively. The observed and analysis results of strain behaviors of the PHWF girder specimens were also compared and discussed in detail.
Keywords: hybrid beam; composite member; prestressed concrete; wide fange; non-linear analysis; Research Subject Categories::TECHNOLOGY